PROTECTION OF INDIVIDUAL AND COLLECTIVE RIGHTS OF EMPLOYEES IN THE EVENT OF CHANGE OF THE EMPLOYER - Kovačević, Tijana R (Glasnik Advokatske komore Vojvodine, 2023)
The paper analyzes in detail how to ensure the protection of individual and collective rights of employees in the event of a change of employer. In this regard, the protection of employees is ensured through the rules on the automatic transfer of employment contracts from the “old” to the “new” employer while maintaining the same working conditions. Hence, the position of employees remains unchanged regardless of changes in the activities carried out by the employer and decisions on undertaking and acquisition of the company. In this sense, the guarantee of job security appears as a counterweight to the management authority of the employer and the freedom of entrepreneurship. The content of the principle of employment security is reflected in the prohibition of initiation of dismissal by the employer as a consequence of structural change. Consequently, the successor employer enters into the rights and obligations of the predecessor employer while preserving the legal status, thus protecting the employees affected by the acquisition. In addition, the legal continuity is not interrupted even when it comes to the rights and obligations arising from the collective labour agreement that continues to produce legal effects with the successor employer.
Keywords: change of employer, company transfer, employment contract